Denial of genocides in the twenty-first century - Der Matossian, Bedross, 1978- (University of Nebraska Press, 2023)
"Denial of Genocides in the Twenty-First Century discusses genocide denial in the twenty-first century by concentrating on communication, social networks, and public spheres of daily life"-- Provided by publisher.
Keywords: Genocide -- History -- 21st century.; Génocide -- Histoire -- 21e siècle.; POLITICAL SCIENCE / Genocide & War Crimes.; SOCIAL SCIENCE / Media Studies.; Genocide; 2000-2099; History